User Perceptions In The Implementation Of The EPuskesmas Information System In Cijulang Puskesmas: Persepsi Pengguna Dalam Implementasi Sistem Informasi EPuskesmas Di Puskesmas Cijulang - Asriyani, Diah; Ulfah Fauziah (Jurnal Rekam Medis dan Informasi Kesehatan, 2024)
The development of globalization, especially in the context of health services, has encouraged the adoption of information technology, such as Electronic Medical Records (RME). Puskesmas as a first level health facility certainly requires information technology that can improve the efficiency and quality of services such as ePuskesmas. The implementation of ePuskesmas has not been fully implemented evenly, there are still obstacles found in its implementation. User perception plays an important role in the successful implementation of ePuskesmas. The aim of this research is to determine user perceptions in implementing the ePuskesmas information system at the Cijulang Community Health Center. This research uses quantitative research methods with descriptive research design, with a sample size of 35 ePuskesmas users with Total Sampling as the sampling technique. Data collection was carried out using a questionnaire. Characteristics of respondents with the most gender were women 94.3%, age category 26-35 years 48.6%, most recent education D3 54.3%, and most working time >3 years 77.1%. Perception of users based on performance expectations of the majority agreed 42.9%, expectation of majority enterprises agreed 54.3%, majority social influence agreed 74.3% and majority facilitating conditions agreed 68.6%.